Planning Extreme Programming - Beck Kent; Fowler Martin (Addison-Wesley Publishing Company, 2001)
This book presents the approaches, methods, discipline, and advice you need to plan and track a successful Extreme Programming project. Foreword, Preface, Acknowledgements, Why Plan?, Fear, Driving Software, Balancing Power, Overviews, Too Much to Do, Four Variables, Yesterday's Weather, Scoping a Project, Release Planning, Writing Stories, Estimation, Ordering the Stories, Release Planning Events, The First Plan, Release Planning Variations, Iteration Planning, Iteration Planning Meeting, Tracking an Iteration, Stand-up Meetings, Visible Graphs, Dealing with Bugs, Changes to the Team, Tools, Business Contracts, Red Flags, Your Own Process, Index.